1999
DOI: 10.1111/j.1472-8206.1999.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic risk associated with the use of iodinated contrast media in interventional cardiology: pathophysiology and clinical aspects

Abstract: A review of the current knowledge of the anti-thrombotic properties of iodinated contrast media (CM) has been conducted. CM are classified according to their chemical structure, either ionic or non-ionic (monomeric or dimeric). Numerous in vitro and in vivo data show that, although all CM have anti-coagulant properties, ionic molecules are more potent than non-ionic and, furthermore, do not activate resting platelets, unlike non-ionic agents. These properties may lead to a decrease in thrombus formation during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Here again there are potential interpretation biases: (i) all types of reactions were recorded, including those which are not related to any anaphylactoid aetiology, (ii) the relative inaccuracy of sales data and (iii) the number of examinations and estimation of the number of examinations with each type of CM. Furthermore, because of its higher anticoagulant and anti-platelet potential [2], ioxaglate was used in a higher percentage of intra-cardiac and intra-arterial (i.a.) procedures than in i.v.…”
Section: Pharmacovigilance Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Here again there are potential interpretation biases: (i) all types of reactions were recorded, including those which are not related to any anaphylactoid aetiology, (ii) the relative inaccuracy of sales data and (iii) the number of examinations and estimation of the number of examinations with each type of CM. Furthermore, because of its higher anticoagulant and anti-platelet potential [2], ioxaglate was used in a higher percentage of intra-cardiac and intra-arterial (i.a.) procedures than in i.v.…”
Section: Pharmacovigilance Datamentioning
confidence: 99%
“…antiplatelet properties [2]. The so-called non-ionic monomers result from the coupling of a tri-iodinated aromatic moiety to polyhydroxylated alkyl side chains.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental observations have shown that nonionic agents have weaker anticoagulant action than ionic agents; both inhibit the platelet activation induced by endogenous agents, but nonionic monomers have significant direct platelet-activating properties [4,[12][13][14][15][16]. However, it is still unclear whether these in vitro data translate into any major adverse clinical effects.…”
Section: Discussion Previous Studiesmentioning
confidence: 99%
“…These can be partially explained in terms of differences in study design, the type of patients, the type of devices, the anticoagulant and antiplatelet regime, and the type and dose of the contrast agents [4]. More recently, Scheller et al [5] demonstrated a significant reduction in the incidence of acute and subacute stent occlusion, when the ionic ioxaglate was compared with six different nonionic contrast agents.…”
Section: Introductionmentioning
confidence: 97%
“…While non‐ionic CM do not inhibit thrombin formation (Fareed et al., 1990), and promote platelet activation (Hardeman et al., 1991), ionic CM has more potent anti‐thrombin and anti‐platelet effects. Thus, a clinical value for the higher anti‐coagulant properties of ionic CM should be expected following local interventional procedures (Grines et al., 1996; Qureshi et al., 1997; Idee and Corot, 1999; Scheller et al., 2001). As all the CM was administered IV, these types of effects could not be elucidated in our study.…”
Section: Discussionmentioning
confidence: 99%